BIOLOGY OF COLLETOTRICHUM SPP. AND EPIDEMIOLOGY OF THE ANTHRACNOSE IN TROPICAL FRUIT TREES - Silva, Christiana de Fátima Bruce da (2013)
The anthracnose is important disease in the pre and postharvest phases. Several species of Colletotrichum (C. gloeosporioides, C. acutatum, C. musae e C. magna) are responsible for inciting this disease. The pathogen infects many fruit trees in tropical and temperate regions, causing considerable damage and loss in all phases of cultures. Characteristic symptoms are dark necrotic lesions depressed, subcircular or angular shaped, and there may be coalescing. Infections have a special feature: the phenomenon of quiescence. This process has important implications, particularly in post-harvest, because the damage from infections reflect only this phase. The intensity of the disease have been striking at temperatures from 24 to 28 °C and in the presence of high relative humidity. The understanding of some aspects of the biology of the pathogen (the process of quiescence) and the epidemiology of the disease is crucial, since much has not yet been fully clarified, especially when the aim is to achieve sustainable management.